Kinetics and mechanisms of the reaction between the pentaamine(dimethylsulfoxide)cobalt(III) complex and the reducing agents chromium(II), vanadium(II) and europium(II) in aqueous solution - de Oliveira, Luiz Antonio Andrade; Toma, Henrique Eisi; Giesbrecht, Ernesto (Eclética Química, 1990)
.